KEBAHAGIAAN SUBJEKTIF PADA WANITA DENGAN PUTTING OUT SYSTEM DI KABUPATEN SIDOARJO - Eky Oktavia Anggraini; Lely Ika Mariyati (Psyche: Jurnal Psikologi, 2020)
This research was motivated by UMKM in Sidoarjo Regency, totaling 2635 businesses involving female workers as employees, one of whom was a homeworker. This study aims to describe the description of women's subjective happiness who work with the putting out system. The method used in this study is qualitative with a case study approach. The subject of this study amounted to 3 women workers with putting out system. Determination of research subjects using purposive sampling technique. Data collection methods using semi-structured interview techniques. The results of the study describe each subject experiencing subjective happiness such as being satisfied with themselves, satisfied with life with family, good relations with peers, optimistic about the future, satisfied with health conditions and enjoying leisure time with family. Each subject has a picture of positive affect as well as feeling happy with the work that is currently occupied and does not cause signs of depression, sadness, despair so that there is no negative affect resulting from working with the putting out system. Keywords: Subjective Happiness, Female Putting Out System Workers, UMKM